Broadband Terahertz Quantum Cascade Laser Dual‐Comb Sources under Off‐Resonant Microwave Injection. Issue 10 (17th July 2022) - Liao, Xiaoyu; Li, Ziping; Zhou, Kang; Guan, Wen; Zhao, Yiran; Wang, Chenjie; Wan, Wenjian; Yang, Sijia; Zhang, Zhenzhen; Wang, Chang; Cao, Juncheng; Zeng, Heping; et al.
Abstract : Broadband dual‐comb spectroscopy has attracted increasing interests due to its unique advantages in high spectral resolution, fast detection, and so on. Although the dual‐comb technique is relatively mature in the infrared wavelengths, it is, currently, not commercially capable of practical applications in the terahertz regime due to the lack of high‐performance broadband terahertz dual‐comb sources. In the terahertz frequency range, the electrically pumped quantum cascade laser (QCL) is a suitable candidate for the dual‐comb operation. Although the resonant microwave injection locking is widely used to broaden the emission spectra of terahertz QCLs, it is challenging to be employed to obtain broadband dual‐comb sources that can fully exploit the laser gain bandwidth due to the large phase noise induced by the resonant injection and nonideal microwave circuits. Herein, an off‐resonant microwave injection to significantly broaden the dual‐comb bandwidth of a terahertz QCL dual‐comb source is used. The measured optical dual‐comb bandwidth is broadened from 147 GHz in free running to > 450 GHz under the off‐resonant injection. By performing a numerical analysis based on a rate equation model, the broadband dual‐comb operation under the off‐resonant microwave injection can result from a wider lasing bandwidth and a higher degree of phase matching. Abstract : It is much demanding to develop broadband dual‐comb sources covering absorption lines of various molecules for spectroscopic and imaging applications. Herein, an off‐resonant microwave injection is employed to significantly broaden the optical bandwidth of a quantum cascade laser dual‐comb source emitting around 4.2 THz. The technique provides a powerful tool to achieve broadband terahertz dual‐comb sources for high‐precision applications.